Development of Mosque Architecture in Islamic Civilization and Its Context in Indonesia - Winarti, Rinni; Al-Obaidi, Khaleel (Jurnal Iman dan Spiritualitas, 2024)
The mosque is a place to worship Allah SWT. Mosques have an important meaning for Muslims because they have a long history and are inseparable from the development of Muslim civilization. As a religious building, the mosque is a representation of the Muslim community that gave birth to and prospered it. Mosques evolve and develop dynamically along with the growth and development of culture in society, presenting two sides of the coin. On the one hand, this dynamic encourages the growth and adaptation of mosques to social and cultural changes. But on the other hand, it presents a problem in understanding the history of the mosque as a whole. The evolution of the mosque also opens up opportunities for deeper exploration of the mosque in order to understand history. By analyzing the development of mosques from various aspects, such as architecture, culture and social roles, we can gain a deeper understanding of the changes and development of mosques in various historical periods in the world and in Indonesia.